LINGUISTIK LANSKAP: MULTILINGUAL PADA TANDA DI RUANG PUBLIK KAWASAN EKOWISATA SUBAK SEMBUNG DENPASAR - I Putu Gede Pradnya Winarta; Ketut Widya Purnawati; Ni Luh Nyoman Seri Malini (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2026)
This qualitative research of linguistic landscapes in Subak Sembung Ecotourism Area Denpasar. in order to understand how written language in the public domain portrays identity and social dynamics. The study uses a sociolinguistic approach to analyze 11 data samples according to the sign creator's category (top-down and bottom-up), the Spolsky and Cooper (1991) taxonomy, and Landry and Bourhis theory of language functions. The study's primary focus is on the use of language and its symbolic and informational functions in public texts at locations that combine traditional agriculture with sustainable tourism. According to research, the majority of public discourse is conducted in Indonesian, followed by English and Balinese. The use of Balinese script as a symbol of local cultural identity reflects the symbolic function, while the informative function is more prominent in the transmission of practical instructions. Nevertheless, there were overlaps in writing techniques and deviations from grammatical rules. The study concluded that, in the context of ecotourism, it is crucial to standardize writing in accordance with national standards and strengthen the Balinese script in order to preserve culture (Landry & Bourhis, 1997).